Aortic Valve Papillary Fibroelastoma Associated with Acute Cerebral Infarction: A Case Report. (10th January 2013) - Takeuchi, Nobuhiro; Takada, Masanori; Fujita, Koichi; Nishibori, Yoshiharu; Maruyama, Takao; Naba, Kazuyoshi
Abstract : An 80-year-old woman with a history of congestive heart failure, atrial fibrillation, and hypertension was transferred to our institution with hematemesis. Her drug regimen included 2 mg warfarin potassium/day to prevent thromboembolic events. Transthoracic echocardiography (TTE) performed at 78 years of age revealed a mass attached to the noncoronary cusp and a cardiac tumor was suspected. The patient declined surgery and was meticulously followed up with periodic TTE. Upper gastroendoscopy revealed a gastric ulcer with an exposed blood vessel; anticoagulant therapy was ceased. On day 15 of admission, acute cerebral infarction occurred. Heparin sodium and warfarin potassium were administered rapidly, and her symptoms improved. TTE revealed no alteration of the mobile, string-like mass attached to the noncoronary cusp. Cardiac tumor was considered the cause of cerebral infarction, and the patient consented to surgical therapy. Pathological examination of the resected tumor suggested papillary fibroelastoma (PFE). Although no guidelines exist for PFE management, a mobile, cardiac tumor necessitates surgical resection to prevent thromboembolic events, even when small in size.